Impact of body mass index on the outcome of catheter ablation of atrial fibrillation. Issue 3 (2nd October 2018) - Glover, Benedict M; Hong, Kathryn L; Dagres, Nikolaos; Arbelo, Elena; Laroche, Cécile; Riahi, Sam; Bertini, Matteo; Mikhaylov, Evgeny N; Galvin, Joseph; Kiliszek, Marek; Pokushalov, Evgeny; Kautzner, Josef; et al.
Abstract : Objectives: The association between obesity and atrial fibrillation (AF) is well-established. We aimed to evaluate the impact of index body mass index (BMI) on AF recurrence at 12 months following catheter ablation using propensity-weighted analysis. In addition, periprocedural complications and fluoroscopy details were examined to assess overall safety in relationship to increasing BMI ranges. Methods: Baseline, periprocedural and follow-up data were collected on consecutive patients scheduled for AF ablation. There were no specific exclusion criteria. Patients were categorised according to baseline BMI in order to assess the outcomes for each category. Results: Among 3333 patients, 728 (21.8%) were classified as normal (BMI <25.0 kg/m 2 ), 1537 (46.1%) as overweight (BMI 25.5–29.0 kg/m 2 ) and 1068 (32.0%) as obese (BMI ≥30.0 kg/m 2 ). Procedural duration and radiation dose were higher for overweight and obese patients compared with those with a normal BMI (p=0.002 and p<0.001, respectively). An index BMI ≥30 kg/m 2 led to a 1.2-fold increased likelihood of experiencing recurrent AF at 12-months follow-up as compared with overweight patients (HR 1.223; 95% CI 1.047 to 1.429; p=0.011), while no significant correlation was found between overweight and normal BMI groups (HR 0.954; 95% CI 0.798 to 1.140; p=0.605) and obese versus normal BMI (HR 1.16; 95% CI 0.965 to 1.412; p=0.112). Conclusions: Patients with a baseline BMI ≥30 kg/m 2 have a higher recurrence rate of AF following catheter ablation and therefore lifestyle modification to target obesity preprocedure should be considered in these patients.